Rahbilitation & Sports Medicine - Beck F; Siefken K; Reimers AK (Deutsche Zeitschrift für Sportmedizin, 2022)
Problem: Physical activity (PA) is a vital component for promoting physical and mental health and for preventing disease. The COVID-19 pandemic has challenged populations from around the world on various levels to maintain and increase overall PA and subsequently led to a shift in physical activity and its health outcomes. This paper synthesizes the current literature on PA during the COVID-19 pandemic in the German population. Methods: In a rapid review we identified 31 studies that examined PA behavior in children, adolescents, young adults and adults from Germany during the COVID-19 pandemic. Results: Findings indicate predominantly a decline in PA among all age groups. PA levels in children and adolescents increased in a few studies predominantly during the first lockdown. Types of sports and intensities changed within the German population during the pandemic. Quality assessment of the included studies revealed a lack of adequately reported PA measures as well as a lack of sufficiently reported study results. Conclusion: The COVID-19 pandemic led to lower PA levels overall in the German population. Furthermore, the PA inequality has been exacerbated. With the uncertainty of the duration of the pandemic, the continuous and cross-agency efforts of PA promotion across all population groups is key. Key Words: Exercise, Sport, Lockdown, SARS-CoV-2